Role of Social Media on Body Image Satisfaction in Young Adults - Vanshika Singhal; Ms. Kriti Bhargava (International Journal of Indian Psychȯlogy, 2022)
This quantitative study examines how young individuals’ perceptions of their bodies are shaped by social media. The study had a sample size of n=152 young adults who were selected at random through the use of a survey approach. The primary hypothesis was to determine the relationship between social media usage and body satisfaction. The study illuminated both positive and negative implications on body image beliefs by providing deep insights into how different social media platforms shape these perceptions. The results shed light on the complex connection between the target audience’s social media use and their body image judgments.